Understanding Perspectives and Practices of "Learning through Play" in East African Refugee and Host-Country Schools - Abraha Asfaw; Silvia Diazgranados; Betty Akullu Ezati; Jonathan Kwok; Christina Raphael; Anne Smiley; Peter Ssenkusu (Journal on Education in Emergencies)
In this article, we investigate understandings and practices of learning through play (LtP) in refugee and host-country contexts in Ethiopia, Tanzania, and Uganda. This is an area in which international donors have increased their investments in recent years. We used a positive deviance approach to select 12 best practice preprimary and primary schools. We used ethnographic methods to study these schools for 14-20 days in order to learn from their existing play-based teaching and learning practices. Our findings draw from the research team's observations, visually stimulated interviews, and focus group discussions with 205 teachers, parents, and headteachers, and 160 students. The findings reveal that most of these education stakeholders (teachers, students, and parents) understood play and formal learning to be mutually exclusive but also recognized the developmental benefits of play. The findings also describe various LtP and LtP-adjacent learning activities, such as guided play and games, storytelling and role-play, energizers, and structured playful learning. The factors found to be critical to the school-based implementation of LtP include supportive policies, school leadership, and parental support, professional development and support for teachers, and addressing schools' capacity and structural limitations. Based on these findings, we recommend that LtP proponents frame LtP as connected to active learning methods in terms of definition, conceptualization, and advocacy for its integration into policy frameworks. We built on the extant constructivist pedagogy and play literature to develop a typology of classroom-based LtP activities with the aim of encouraging policymakers, practitioners, and researchers to strengthen education systems' ability to provide targeted support for teachers that will enable them to gradually increase their implementation of quality LtP practices across typology zones.